Dosimetric Evaluation of Very High Energy Electron (VHEE) Beams in the Male Pelvic Region Using Geant4/TOPAS - Essaidi, E. M.; Krim, M.; Kaanouch, O.; Tantaoui, M.; Mesradi, M. R.; Abdessamad, D.; Benchekroun, D. (National Research and Innovation Agency, 2025)
The CLEAR (CERN Linear Electron Accelerator for Research) facility has significantly advanced high-energy electron radiotherapy, particularly for treating deep-seated tumors. However, achieving precise and accessible treatment delivery while minimizing damage to surrounding healthy tissues remains challenging. Very High Energy Electrons Beam (VHEE) offer notable potential due to their deep penetration capabilities. However, their nearly uniform dose distribution raises concerns about unintended exposure to healthy tissues. A key innovation in this field is the use of focused VHEE beams, which deliver a concentrated dose to a small defined area at a high dose rate, potentially enhancing treatment precision. This study evaluates the dosimetric characteristics of focused VHEE beams compared to collimated beams using GEANT4/TOPAS Monte Carlo simulations. A beamline with two quadrupole magnet triplets was designed to focus VHEE beams on a water phantom, simulating clinical conditions. The findings show that focused VHEE beams increased the dose to the prostate by 5.24 % while significantly reducing the dose to adjacent organs at risk: 16.93 % to the bladder, 50.81 % to the rectum, and 68.75 % to the femoral heads. These reductions highlight the dosimetric advantage of focused VHEE beams in sparing non-targeted tissues. While these results underscore the potential benefits of focused VHEE beams for deep-seated tumor treatment, additional research, including clinical validation and patient-specific modeling, is essential to fully evaluate their clinical utility. This study lays the groundwork for optimizing VHEE beam applications in cancer therapy by demonstrating improved dose delivery accuracy and reduced risk to adjacent organs.